Literatur review: Analisis perbandingan literasi sejarah di Australia dengan Indonesia - Nafi'ah, Ulfatun; Purwanta, Hieronymus (Historiography: Journal of Indonesian History and Education, 2024)
Abstract This article aims to compare historical literacy in Australia with Indonesia. The purpose of writing the article is to understand the similarities and differences in historical literacy in Australia and Indonesia. This study uses a literature review method on Scopus journal. Articles published between 2010-2024. The results were 36 documents about historical literacy in Australia and 13 journal articles about historical literacy in Indonesia. A total of 20 articles were analyzed in more depth because they were appropriate to the topic. The result is that historical literacy in Indonesia is still low, both at secondary and tertiary levels. The goals of historical literacy in Australia and Indonesia have similarities, namely increasing students' historical awareness of the concept of critical historical thinking. The use of digital media is important to improve historical literacy, in Indonesia using various digital media such as the web, historical YouTube, films, e-modules, and multimedia. In Australia, movies and e-books are used. For learning methods in Australia, the PAPA model, and receptive and productive models are applied. In Indonesia, increasing historical literacy uses the "like a historian" model, the READI model, the "brainwriting" model, and the Scholarship of Teaching and Learning (SoTL) model.Abstrak Artikel ini bermaksud untuk membandingkan literasi sejarah di Australia dengan Indonesia. Tujuan penulisan artikel adalah untuk memahami persamaan dan perbedaan literasi sejarah di Australia dan Indonesia. Kajian ini menggunakan metode literature review terhadap artikel jurnal scopus yang terbit antara tahun 2010-2024. Hasilnya diperoleh 36 dokumen tentang literasi sejarah di Australia dan 13 artikel jurnal tentang literasi sejarah di Indonesia. Sebanyak 20 artikel dianalsisi secara lebih mendalam karena sesuai dengan topik. Hasilnya literasi sejarah di Indonesia masih rendah, baik di tingkat menengah dan perguruan tinggi. Tujuan literasi sejarah di Australia dan Indonesia memiliki persamaan yaitu meningkatkan kesadaran sejarah siswa dengan konsep berpikir sejarah secara kritis. Penggunaan media digital menjadi penting untuk meningkatkan literasi sejarah, di Indonesia menggunakan berbagai media digital seperti web, youtube sejarah, film, e-modul dan multimedia. Di Australia menggunakan media film, dan e-book. Untuk metode pembelajaran di Australia menerapkan model PAPA, model reseptif, dan produktif. Di Indonesia peningkatan literasi sejarah menggunakan model “like a historian”, model READI, model “brain writing” dan model Scholarship of Teaching and Learning (SoTL).